2021
DOI: 10.1039/d1sc01450a
|View full text |Cite
|
Sign up to set email alerts
|

Discovering protein–protein interaction stabilisers by native mass spectrometry

Abstract: Stabilising protein–protein interactions is challenging, yet therapeutically important. Native mass spectrometry can be used to monitor binding equilibria, allowing identification and measurement of novel protein–protein interaction stabilisers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…14-3-3 protein binding can regulate expression of other molecules [ 88 ] and modify interaction networks. [ 8 ] Many 14-3-3 and 14-3-3 PPIs inhibitors [ 89 , 90 , 91 ] and stabilizers [ 92 , 93 , 94 , 95 ] have been regarded as potential therapeutic targets in other systems than heart [ 22 , 23 ]. Small molecules, peptides and natural products that target 14-3-3 or 14-3-3 PPIs have been applied as 14-3-3 and 14-3-3 PPI modulators [ 96 , 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…14-3-3 protein binding can regulate expression of other molecules [ 88 ] and modify interaction networks. [ 8 ] Many 14-3-3 and 14-3-3 PPIs inhibitors [ 89 , 90 , 91 ] and stabilizers [ 92 , 93 , 94 , 95 ] have been regarded as potential therapeutic targets in other systems than heart [ 22 , 23 ]. Small molecules, peptides and natural products that target 14-3-3 or 14-3-3 PPIs have been applied as 14-3-3 and 14-3-3 PPI modulators [ 96 , 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches not discussed here (e.g., microscale thermophoresis ( Centorrino et al, 2022 ; Kozeleková et al, 2022 ), differential scanning fluorimetry ( Cossar et al, 2021 ; Waløen et al, 2021 ; Joshi et al, 2022 ), analytical ultracentrifugation ( Horvath et al, 2021 ; Leysen et al, 2021 ; Neves et al, 2021 ; Pohl et al, 2021 ; Srdanović et al, 2022 ), single angle x-ray scattering ( Kast and Dominguez, 2019 ; Leysen et al, 2021 ) also contribute new understanding and support hypotheses. NMR ( Kuusk et al, 2019 ; Neves et al, 2021 ) and native mass spectrometry ( Bellamy-Carter et al, 2021 ) are also important techniques that shows great promise for studying 14-3-3 PPIs. Ultimately, a full understanding of 14-3-3 function will only be achieved by taking an interdisciplinary approach whereby high quality biophysical data complements unexplored single molecule approaches, together with structural and cellular biology studies.…”
Section: Discussionmentioning
confidence: 99%
“…This work has shown that nMS can show these complexes with intact proteins, in addition to the model peptides which have previously been used. [16] nMS was able to directly show the existence of the IMiD ternary complexes, which will be beneficial in the screening of small molecule libraries for further glues that modulate this interaction.…”
Section: Bodymentioning
confidence: 99%
“…nMS is effective in separating individual species that exist in a stoichiometric mixture, capturing transient interactions, and comparing stability of complexes. [12][13][14] Whilst nMS has previously been used to predict the efficacy of PROTACs [15] and to analyse complexes formed between MGs and model peptides [16], this is the first example of its application to MGs and multimeric E3 complexes. We have demonstrated its efficacy using disease relevant drugs and targets; two E3 ligase proteins (CRBN:DDB1 and DCAF15:DDA1:DDB1), five molecular glues (lenalidomide, thalidomide, pomalidomide, E7820, and indisulam), and two POIs (GSPT1 and RBM39).…”
Section: Bodymentioning
confidence: 99%